2021
DOI: 10.3389/fgene.2021.703860
|View full text |Cite
|
Sign up to set email alerts
|

Non-Coding RNA Networks in Pulmonary Hypertension

Abstract: Non-coding RNAs (ncRNAs) are involved in various cellular processes. There are several ncRNA classes, including microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs). The detailed roles of these molecules in pulmonary hypertension (PH) remain unclear. We systematically collected and reviewed reports describing the functions of ncRNAs (miRNAs, lncRNAs, and circRNAs) in PH through database retrieval and manual literature reading. The characteristics of identified articles, especially t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 158 publications
0
9
0
Order By: Relevance
“…Transcript regulation in this manner has broad potential for cancer treatment by modulating the expression of therapeutic targets in a tunable and temporally restricted manner that does not rely on the development of small molecule ligands. This technology could equally be applied in the treatment of rare genetic diseases to control the production of toxic proteins as in Huntington’s Disease, or in modulating any other RNA-mediated process including (but not limited to) hypertension, pain, and cell–cell communication [ 239 , 240 , 241 ]. The fusion of Cas7-11 to ADAR2 has already been used for efficient base editing in mammalian cells, suggesting additional applications in the treatment of genetic diseases caused by discrete heritable mutations [ 16 ].…”
Section: Emerging Applications Of Crispr-cas In Rna Editingmentioning
confidence: 99%
“…Transcript regulation in this manner has broad potential for cancer treatment by modulating the expression of therapeutic targets in a tunable and temporally restricted manner that does not rely on the development of small molecule ligands. This technology could equally be applied in the treatment of rare genetic diseases to control the production of toxic proteins as in Huntington’s Disease, or in modulating any other RNA-mediated process including (but not limited to) hypertension, pain, and cell–cell communication [ 239 , 240 , 241 ]. The fusion of Cas7-11 to ADAR2 has already been used for efficient base editing in mammalian cells, suggesting additional applications in the treatment of genetic diseases caused by discrete heritable mutations [ 16 ].…”
Section: Emerging Applications Of Crispr-cas In Rna Editingmentioning
confidence: 99%
“…miRs are small noncoding RNAs, approximately 21-23 nucleotides in length, that repress the expression of targeted genes by binding to the 3′ untranslated region of the target gene [ 70 ]. In addition, many studies have found that miRNA is related to VSMC proliferation and vascular remodeling [ 71 ]. Here are some examples of which miRNA are involved in vascular remodeling.…”
Section: Effect Of Micrornas On Vsmcsmentioning
confidence: 99%
“…Aside from miRNAs, lncRNAs and circRNAs are other two major groups of ncRNAs relatively less investigated and understood in the PH field. However, they are attracting growing attention due to their abundance, regulatory functional roles, cell/tissue expression specificity in human diseases, and potential therapeutic targets and disease biomarkers [ 18 , 19 , 20 , 21 ]. This review focuses on the recent developments of lncRNA and circRNA related to PH.…”
Section: The Noncoding Rna Transcriptome In Pulmonary Hypertensionmentioning
confidence: 99%